2021
DOI: 10.1155/2021/5552791
|View full text |Cite
|
Sign up to set email alerts
|

Application of Modified Hoek–Brown Strength Criterion in Water-Rich Soft Rock Tunnel

Abstract: When a tunnel is excavated in the water-rich soft rock stratum, the strength of the soft rock is greatly reduced due to the seepage of groundwater. The condition may result in engineering accidents, such as large deformation, limit invasion, and even local collapse of the tunnel. Therefore, it is very important to research the stability of the surrounding rock in the water-rich soft rock tunnel. The water-rich disturbance factor considering the seepage influence of groundwater and blasting disturbance is propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Rock is a kind of discontinuous medium, so the physical and mechanical properties will change greatly under the influence of complex geological conditions, such as groundwater and high geostress [1][2][3]. If these changes are not considered in construction, the stability of underground engineering will be greatly affected [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Rock is a kind of discontinuous medium, so the physical and mechanical properties will change greatly under the influence of complex geological conditions, such as groundwater and high geostress [1][2][3]. If these changes are not considered in construction, the stability of underground engineering will be greatly affected [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The results of Li et al [7] indicated that the dynamic characteristics of regional groundwater and the temporal and spatial evolution of seepage field under the influence of tides must be considered in engineering construction. The results of Deng et al [8] showed that when excavating tunnels in water-rich soft rock formations, the infiltration of groundwater greatly reduced the strength of the soft rock. The results of Wang et al [9] show that the influence of groundwater on tunnel engineering is very complex.…”
Section: Introductionmentioning
confidence: 99%